The rights and obligations of the pastor of a parish according to the Code of Canons of the Eastern Churches and the Particular Law of the Syro-Malabar Church - Adoppillil, Thomas Mathew (University of Ottawa (Canada), 2003)
This study consisting of five chapters is an examination of the rights and obligations of the pastor of a parish according to the Code of Canons of the Eastern Churches and the Particular Law of the Syro-Malabar Church The following important issues constitute the core of the investigation pursued by the study: the juridical figure of the pastor of a parish in the Eastern tradition; the rights and obligations of the pastor of a parish as minister of the word of God, sanctification and governance; and the rights of the pastor of a parish in his removal and transfer from office. The pastor of a parish, both theologically and juridically, is at the center of a parish community. He is a presbyter, the foremost collaborator of the eparchial bishop in the parish and he carries out his ministry under the authority of the same eparchial bishop. The pastor is the good shepherd of the flock, teacher in matters of faith, preacher of the word of God, mediator and principal dispenser of the mysteries of God who has the right and obligation to encourage, coordinate and direct the catechetical formation of the faithful entrusted to his care. It is his primary responsibility for the sanctification of the faithful and he is obliged to motivate, inspire and organize his parishioners in a way that they will in fact live out "the sacraments and sacramentals" in their daily life. Pastor shares in the governing function of the eparchial bishop and assumes responsibilities of organizing, directing and coordinating the faith life of the parish community. His office does not entail legislative and judicial power. The Eastern Code and the particular law of the Syro-Malabar Church make provision for the pastor to exercise the executive power of governance especially in the area of dispensation from merely ecclesiastical laws, such as the laws governing matrimonial impediments under certain conditions and circumstances, blessing of marriages, dispensation from private vows and oaths, and the administration of the parish's temporal goods. The pastor is obliged to know his flock, promote Christian values both in individual members and in associations, and should make sure that the needy and the destitute are never ignored. All these responsibilities of the pastor of a parish are part of his function of organizing and directing the life of the faithful. It is the pastor's responsibility to arouse interest among his parishioners to be involved in the good of the community. Through legitimate appointment to his office, the pastor acquires certain rights related to the security and stability of the office as well as his well-being and good name. A bishop cannot arbitrarily remove or transfer a pastor who has been appointed either for an indefinite period of time or for a determined period. Any substantial violation of the right of defense of a pastor could result in the invalidity of the bishop's decision. The study concludes that a pastor of a parish does have concrete rights and corresponding obligations in the Church, and these rights and obligations are real and not merely empty words. These rights and obligations are embedded in the threefold mission of the Church, namely the teaching, sanctifying and governing functions.
Keywords: Religion, Clergy.